Open circuit potential as a tool for the assessment of binding kinetics and reagentless protein quantitation - Sharafeldin, M; James, T; Davis, JJ (American Chemical Society, 2021)
A microfluidic open circuit potential label-free protein assay was developed for the reagentless quantification of C-reactive protein (CRP), a model protein target, and further utilized to assess target-receptor binding kinetics. Generated sensors have very high baseline stabilities (<1% change in 100 min) and high levels of selectivity in complex media. Real-time assays are fast (<20 min), of high sensitivity (1 ng/mL limit of detection for CRP in serum), and resolve kinetic and thermodynamic characteristics that correlate well with those resolved optically. The assay shows excellent correlation with an enzyme-linked immunosorbent assay analysis of patient samples. The methodology has value in potentially underpinning a low-cost, rapid, and sensitive single-step biomarker quantification.